2019
DOI: 10.1105/tpc.19.00057
|View full text |Cite
|
Sign up to set email alerts
|

The Ca2+ Channel CNGC19 Regulates Arabidopsis Defense Against Spodoptera Herbivory

Abstract: Cellular calcium elevation is an important signal used by plants for recognition and signaling of environmental stress. Perception of the generalist insect, Spodoptera litura, by Arabidopsis (Arabidopsis thaliana) activates cytosolic Ca 21 elevation, which triggers downstream defense. However, not all the Ca 21 channels generating the signal have been identified, nor are their modes of action known. We report on a rapidly activated, leaf vasculature-and plasma membrane-localized, CYCLIC NUCLEOTIDE GATED CHANNE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 90 publications
(131 reference statements)
3
74
0
Order By: Relevance
“…The MAMP‐induced stomatal closure is abolished in mutants that loss of function of MPK3/6 or their upstream MKK4/5 independently of abscisic acid (ABA) signaling (Su et al 2017). Moreover, the SERK family RLKs positively regulate stomatal closure by transmitting immune signals from PRR complex to downstream MAPKKK protein YDA (Meng et al 2015). Importantly, recent studies demonstrated that PRR complex can also regulate stomatal closure through a short signals transduction module.…”
Section: Recent Discoveries Of the Activation Of Immunity Mediated Bymentioning
confidence: 99%
“…The MAMP‐induced stomatal closure is abolished in mutants that loss of function of MPK3/6 or their upstream MKK4/5 independently of abscisic acid (ABA) signaling (Su et al 2017). Moreover, the SERK family RLKs positively regulate stomatal closure by transmitting immune signals from PRR complex to downstream MAPKKK protein YDA (Meng et al 2015). Importantly, recent studies demonstrated that PRR complex can also regulate stomatal closure through a short signals transduction module.…”
Section: Recent Discoveries Of the Activation Of Immunity Mediated Bymentioning
confidence: 99%
“…Phosphorylation of AtCNGC2/4 by AtBIK1 is critical for calcium spiking in response to immune elicitors (Tian et al, 2019). The related channel proteins AtCNGC19 and 20 have recently been implicated in regulation of AtBAK1-dependent cell death containment in plant immunity (Yu et al, 2019), and AtCNGC19 has further been shown to have a role in resistance against insect herbivory (Meena et al, 2019). It is not yet known if BIK1 also has a role in activating AtCNGC19 and AtCNGC20.…”
Section: Post-translational Modifications In Early Immune Signalingmentioning
confidence: 99%
“…Like CNGC2 and CNGC4, the two closely related group-I channels CNGC11 and CNGC12 have been implicated in immunity and PCD (Yoshioka et al, 2006;Moeder et al, 2011). Likewise, a role in immunity, wound signaling, and insect resistance has been proposed for CNGC19 and CNGC20, which comprise subclade IVa in the CNGC family (Moeder et al, 2011;Meena et al, 2019). BAK1 and SERK4 are involved in a wide variety of physiological phenomena and the bak1-4 serk4-1 double mutant develops severe postembryonic lethality due to hyperactivation of PCD (He et al, 2007;de Oliveira et al, 2016).…”
Section: Regulation Of Cngc Activation and Turnover By Phosphorylationmentioning
confidence: 99%